A COMPARATIVE STUDY OF LITERARY MOVEMENTS IN 20TH CENTURY EUROPE - Zokirovа Zaynab, Chirchik Stаtе Pеdаgоgicаl Univеrsity Tоurism fаculty Fоrеign lаnguаgе аnd litеrаturе:Еnglish. Sciеntific supеrvisоr: Xamitov Eldor, Еnglish tеаchеr, Chirchik Stаtе Pеdаgоgicаl Univеrsity (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Invites an exploration of how different literary movements across Europe influenced, intersected, and differed from each other during the 20th century. This period was marked by significant social, political, and cultural changes, which deeply shaped the literature and art of the time.